2017
DOI: 10.3892/etm.2017.5258
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl‑chitosan attenuates inducible nitric oxide synthase and promotes interleukin‑10 production in rat chondrocytes

Abstract: Abstract. Osteoarthritis (OA) is a common age-related degenerative joint disease, which is caused by the breakdown of joint cartilage and the underlying bone. Carboxymethyl (CM)-chitosan is a soluble derivative of chitosan that has similar physicochemical properties to the extracellular proteoglycans identified in hyaline cartilage. Previous studies have demonstrated that CM-chitosan serves a protective role in a rabbit OA model. The aim of the present study was to investigate the effect of CM-chitosan on NO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Lactobacillus rhamnosus GR-1 supernatant was able to increase IL-10 output and activated the JAK/STAT pathway to exert an anti-inflammatory property in lipopolysaccharide-stimulated placental trophoblast cells [34]. Carboxymethyl chitosan could attenuate inducible nitric oxide synthase and protect against osteoarthritis through the IL-10/JAK1/STAT3 pathway [35]. The expression of IL-10 could inhibit the expression of proinflammatory mediators such as cell surface receptors, chemokines, and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus rhamnosus GR-1 supernatant was able to increase IL-10 output and activated the JAK/STAT pathway to exert an anti-inflammatory property in lipopolysaccharide-stimulated placental trophoblast cells [34]. Carboxymethyl chitosan could attenuate inducible nitric oxide synthase and protect against osteoarthritis through the IL-10/JAK1/STAT3 pathway [35]. The expression of IL-10 could inhibit the expression of proinflammatory mediators such as cell surface receptors, chemokines, and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…NO as an inflammatory mediator and catabolizing factor is closely related to the damage of cartilage, which can inhibit proteoglycan and COL2A1 synthesis and induce matrix metalloproteinase (MMP S ) synthesis in chondrocytes. High NO concentrations significantly induce chondrocyte apoptosis and decrease chondrocyte vitality [39, 40], so inhibition of NO production is a potential strategy for the treatment of cartilage damage. In this study, the outcomes showed that overexpression of IGF-1 and miR-140 inhibits NO production, inhibits apoptosis, and promoted chondrocyte against of IL-1 β antiproliferative effect, and IGF-1 and miR-140 jointly significantly enhance these effects both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that chondrocytes cultured in CS-alginate beads reduce the expression of inflammatory cytokines (IL-6 and IL-8) and increase cartilage matrix components (hyaluronan and aggrecan) synthesis in vitro, in comparison to alginate beads alone [86]. CS derivative carboxymethyl-CS in a dose-dependent manner reduced the inflammatory profile of primary rat chondrocytes by reducing iNOS expression and upregulating the anti-inflammatory cytokine IL-10 in vitro [87]. In another study, the addition of hyaluronic acid-CS NPs to a pellet co-culture of the human infrapatellar fat pad (IPFP)-derived mesenchymal stem cells (MSCs) with osteoarthritic chondrocytes increased chondrogenic differentiation [88].…”
Section: Cartilagementioning
confidence: 95%